2011
DOI: 10.1007/s00442-011-2205-8
|View full text |Cite
|
Sign up to set email alerts
|

Multitrophic effects of experimental changes in plant diversity on cavity-nesting bees, wasps, and their parasitoids

Abstract: Plant diversity changes can impact the abundance, diversity, and functioning of species at higher trophic levels. We used an experimental gradient in grassland plant diversity ranging from 1 to 16 plant species to study multitrophic interactions among plants, cavity-nesting bees and wasps, and their natural enemies, and analysed brood cell density, insect diversity (species richness), and bee and wasp community similarity over two consecutive years. The bee and wasp communities were more similar among the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 70 publications
5
87
3
1
Order By: Relevance
“…Thus our results support the resource heterogeneity and more individuals hypotheses for wasps, but not for bees. Ebeling et al (2012) also found no relationship between plant diversity and brood cell densities Notes: Values of parameters from REML models, with strips as random factors and the plant composition in the different subplots included as a correlation structure. Abbreviations as in Table 1. v www.esajournals.org of bees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus our results support the resource heterogeneity and more individuals hypotheses for wasps, but not for bees. Ebeling et al (2012) also found no relationship between plant diversity and brood cell densities Notes: Values of parameters from REML models, with strips as random factors and the plant composition in the different subplots included as a correlation structure. Abbreviations as in Table 1. v www.esajournals.org of bees.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the architecture of the vegetation can override the effects of plant diversity on food-web complexity. In contrast to other analyses that simply treated species diversity (e.g., Albrecht et al 2007, Tylianakis et al 2007, Haddad et al 2009, Scherber et al 2010a, Ebeling et al 2012, we accounted for plant composition by including a correlation structure in the residuals of the mixed-effect models. This is important because a change in plant diversity cannot be achieved without altering plant composition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tephritid infestation rate and insect load both decreased with increasing plant diversity (functional group or species richness), which means the increase in parasitism could also be driven by decreasing host density. This response was reported in a study on trap nesting bees on the same field site (Ebeling et al., 2012). However, such an effect seems less likely as an explanation of our results because we found that tephritid infestation rate did not affect parasitism rate.…”
Section: Discussionmentioning
confidence: 99%